Analisis Pengaruh Kredit Ketahanan Pangan dan Energi (KKP-E) Terhadap Pendapatan Petani Ternak di Kabupaten Wonogiri - Utomo, Eko Budi (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.1, Februari 2019 (pp. 1-107)DO - 10.24843/JEKT.2019.v12.i01.p02, 2018)
This research aimed to analyze the effect of Credit Food and Energy (KKP-E) to income of the cattle fattening business in Wonogiri District. Basic method of research is descriptive analysis method and implementation of research conducted by survey method. This research will be conducted in Wonogiri District. Samplingtechnique was used multistage cluster random sampling method. The resultsshowed that relationship between the factors with cattle farmers’s income can beexpressed in multiple linear regression models as follows: Y = 15178510.19 + 3713035.14 X 1 + 362495.26 X 2 + 169794.77 X 3 + 315220.14 X 4 - 125964.84 X 5 - 451.03 X 6 - 151.90 X 7 + 2183539.09 D 1 - 2157838.42 D 2 + e.The results of the regression analysis showed that number of livestock ownership, Breeding experience, Cost of feed, Cost of drugs and use of KKP-E have significant effect on cattle farmers' income, whereas the number of family members, Level of education, age of farmers and Land ownership factor did not significantly affect tocattle farmers' income.
Keywords: Pendapata, KKP-E, Peternakan Sapi Potong